Celah Hukum dalam Asuransi Kecelakaan Kerja - Pratama, Din Eri; Syafaat, Muhammad Arif; Apriani, Rani (Peneliti.net, 2025)
The protection of workers who experience work accidents in Indonesia has been regulated in various regulations, such as Government Regulation Number 49 Year 2023 (PP49/23). However, in practice, there is still a legal vacuum that results in some workers, especially freelancers, not getting proper coverage. This study analyzes the case of a worker who suffered permanent disability due to a work accident, but did not receive appropriate compensation from the company. Using a juridical-normative approach and case analysis, this study finds that loopholes in the legal system and weak supervision mean that workers' rights are not fully met. Therefore, there is a need to revise policies and improve supervision mechanisms so that every worker, regardless of employment status, receives optimal legal protection